Engineering-Based Waterfront Redevelopment of Cipondoh Lake in 2022: An Adaptive Construction Approach for Urban Water Bodies - Luki Haidir Ali; Satyanto Krido Saptomo; Moh. Yanuar Jarwadi Purwanto (Jurnal Indonesia Sosial Sains, 2026)
The 2022 redevelopment of Situ Cipondoh represents an engineering-based waterfront intervention aimed at improving public space quality, socio-economic functions, and environmental conditions within an urban water body. This study documents and analyzes the technical implementation of adaptive construction methods in shallow-water environments, contributing to the body of knowledge on sustainable waterfront infrastructure development in densely populated urban areas. The project focused on the arrangement of key waterfront areas, construction of a flying-deck jogging track, development of a floating market for vendor relocation, and light water normalization. This paper applies a descriptive-analytical approach using construction documentation from 2022, supported by field observations, technical specifications analysis, and post-construction evaluation to assess the effectiveness of the engineering solutions implemented. The results show that the application of a flying-deck structure supported by mini piles installed from a pontoon constitutes an adaptive engineering solution suitable for aquatic environments with soft soil conditions and limited terrestrial access. Vendor relocation to the floating market improved spatial order while maintaining local economic activities and providing formal trading infrastructure compliant with hygiene and safety standards. Overall, the redevelopment enhanced public comfort, visual quality, tourism activity, and regional asset protection while demonstrating replicable engineering approaches for similar urban waterfront contexts.